The Selection of Escort Helicopter to Support Operational Ready Force Navy with Analytical Network Process (ANP) Method - John Zacharias Adu , John Zacharias Adu; Sumantri, Rudi; Herman, Juli (Journal of Industrial Engineering & Management Research, 2024)
Indonesia's strategic geographical position fuels the critical role of national waters in the world economy. This geographical potential has consequences for Indonesia's maritime security. As a naval defence force, the Indonesian Navy is tasked with defending national jurisdiction, enforcing the law, supporting foreign policy, and developing naval power. The Navy's current power development focuses on achieving optimal operational readiness (operational ready force) by increasing mobility, combat power, and alert capability in facing actual and potential threats. One of the priorities in developing the Navy's defence equipment is the procurement of transport/escort helicopters to support the landing of Pasrat (GKK Lintas Heli) in Amphibious Operations. Therefore, this research aims to analyse the selection of escort helicopters to support the Navy's operational ready force using the Analytical Network Process (ANP) method. The ANP method is a new approach in the decision-making process that provides a general framework for treating decisions without making assumptions about the independence of elements at higher levels from elements at lower levels and about the independence of elements within a level. The escort helicopter alternatives selected in this study are Airbus EC-665, Bell AH-1Z, Boeing AH-64E, and TAI T-129, which have essential factors including range, speed, weapons, and sensors. The analysis results show that the main criterion in selecting escort helicopters is the weapon factor, and the best helicopter is Airbus EC-665' Tiger'.